Formulación de un plan de negocio de una cafetería en el Copey Cesar - Parra Daza, Josè Guillermo (Universidad Antonio Nariño, 2023)
In Colombia, coffee consumption increases more and more every day, so taking into account account the lack of cafeterias in coffee-producing and consuming municipalities, design a cafeteria line as the initial headquarters of the project in the municipality of El Copey - Cesár, where the coffee products of this region are made known. Thus giving way to the creation of a company aimed at the cafeteria market in Colombia, having as purpose that the communities appropriate the love for the products purely Colombians, generating that high quality coffee, in addition to being exported, is marketed for satisfy the need of consumers for good coffee in the national territory, the cafeteria will be Aimed at all kinds of people and between the ages of 28 and 64, it will be located on the main street from the center of this municipality where it will have opening hours from 5 in the morning until 9 at night, in this way all the people who go to work in the morning they will have the opportunity to try and taste a good coffee. The background references of coffee production in Colombia, analyzed account for consumption and production international. At the same time, it is important to say that the descriptive approach is taken for the methodology. of the project, using primary and secondary sources, such as surveys, books, videos among others.